Our Experience with Supratracheal Partial Laryngectomy in Advanced Laryngeal Cancer: A Report of Five Cases - Bora Başaran; Can Doruk; Levent Aydemir (Turkish Archives of Otorhinolaryngology, 2020)

(untitled)
Supratracheal laryngectomy (STL) is the ultimate option in conservation surgery, and can be used as an alternative to total laryngectomy in selected tumors. This case series is the first report from Turkey that analyzes the oncological and functional outcomes of STL along with a literature review. Files of five patients who underwent STL between June 2016 and June 2019 were analyzed. Primary tumor findings, postoperative pathology reports, treatment modalities and oncological and functional outcomes of the surgical intervention were noted. Two patients were operated on for horse-shoe glottic tumors with subglottic extension, one patient for primary subglottic mass and two for transglottic ventricular tumors with anterior subglottic extension. Pathological stage of two patients was T3, and of three patients was T4a due to thyroid cartilage invasion. No neck metastases were observed. Three patients with T4a primary tumor were treated with adjuvant radiotherapy. All patients were found disease free in their last follow-up visit. Nasogastric tube was removed in the 1st postoperative month in all patients. While one patient remained tracheostomized in the follow-up period, the remaining four were decannulated. This technique can be used as an alternative to total laryngectomy especially in selected cases with subglottic extension.